The Concept of the Lithuanian-Latvian Border Region - Noreikaitė, Auksė (Acta humanitarica academiae Saulensis, 2023)
The object of the article is the border territory on the side of the Republic of Lithuania, called Palatvijys, and its concept. The aim is to find out what criteria can be used to distinguish this Lithuanian-Latvian border region and reveal the most significant features. Information found in dictionaries, the press, legal documents, various scientific literature, as well as empirical material collected by the author in several stages (in 2008-2019) were used to reveal the topic. The methods applied in this research were qualitative content analysis, case analysis, interpretive methods, and quantitative analysis. The theoretical approaches of geographers, anthropologists, and sociologists talking about the construction of regions and identity were relevant for the analysis of the topic. The Lithuanian-Latvian border is undoubtedly a unique territory, where the cultural environment of the border and the “sense of place” of the inhabitants have been formed for many centuries. We can accurately define only the length of the Lithuanian-Latvian border region, which coincides with the state land border – 588.09 km, and its width differs both in the concepts of residents and in the studies of scientists. However, social and humanities sciences allow us to talk about a region that is not defined by physical boundaries and is changing, constructed according to various socio-cultural criteria. For this reason, the boundaries of the Lithuanian-Latvian region are relative, in their concept it is important to take into account the emic approach, i.e. how the local people understand and value the boundaries. This article is the first attempt to present the Lithuanian-Latvian border area or Palatviiys as a region. In further research, it would be appropriate to delve more deeply into the cultural features of this region, which were formed by the interaction of Lithuanians, Latvians, and Germans, as well as to analyse social relations – communication between Lithuanians and Latvians, movement on both sides of the border, and the expression of regional identity, especially semi-Latvian (skerslatviai) identity.